Hedonistic Motif in Plato’s Phaedo – Olympiodorus’ Simplification - Pacewicz, Artur (Peitho. Examina Antiqua, 2014)
While the aim of the present paper is to analyze Olympiodorus’ commentary to Plato’s Phaedo, particular attention will be paid here to the role of hēdonē. The first part of the text presents the four conceptions of the pleasure that can be found in Plato’s dialogue. Although pleasure does not play the most prominent role either in the Plato’s dialogue or in the Neoplatonic commentary, Olympiodorus’ attitude to this issue reveals an important change and difference between the philosophical views of Plato and those of Olympiodorus. The latter does not seem to discern the possibility that pleasure can have its spiritual dimension (which Plato regards as possible). Thus, the experience of hēdonē is reduced solely to the sphere of the senses and even in this area its role needs to be minimized: in this form it has to be carefully measured and controled. Furthermore, Olympiodorus does not see that so-called hedonistic calculus: whilst it is not strictly speaking connected with virtuous actions, it still can have some significance for the the philosopher’s life.